H2S Sensing and Splitting on Atom‐Functionalized Carbon Nanotubes: A Theoretical Study. Issue 3 (26th February 2018) - Liao, Ting; Kou, Liangzhi; Du, Aijun; Chen, Lingna; Cao, Can; Sun, Ziqi
Abstract: Strategies that can manipulate the electronic and chemical properties of carbon nanotubes (CNT) to meet a target application are challenging, and the introduction of atom functionalization is one path toward this goal. Herein, two types of Fe‐atom‐functionalized CNTs, Fe‐adsorbed CNTs (Fe@CNT) and Fe‐welded CNTs, the latter is a new hybrid material combining the merits of both carbon nanotubes and functional welding metals, are examined in terms of their sensitivity toward detecting hydrogen sulfide (H2 S) and their selective activity toward chemically converting H2 S into valuable fuel resources, for example, elemental sulfur and H2, in the framework of density functional theory (DFT) and the non‐equilibrium Green's function (NEGF) method. The catalytic center formed by the metal and the neighboring under‐coordinated carbon atoms in the Fe‐welded CNT provide an easy pathway for the splitting reaction of H2 S molecules and sheds light on the design of efficient atom‐functionalized nanomaterials for other challenging chemical reactions. Abstract : The facilitated effect on the H2 S splitting process of carbon networking with under‐coordinated carbon atoms around metal sites is properly addressed and rationalized. These findings help to provide valuable information for the development and design of new functionalized nanomaterials for the selective H2 S catalytic reaction and other challenging chemical reactions.